2015
DOI: 10.1097/adm.0000000000000101
|View full text |Cite
|
Sign up to set email alerts
|

Methamphetamines and Pregnancy Outcomes

Abstract: Introduction Methamphetamine (MA) is one of the most commonly used illicit drugs in pregnancy, yet studies on MA-exposed pregnancy outcomes have been limited because of retrospective measures of drug use, lack of control for confounding factors: other drug use, including tobacco; poverty; poor diet; and lack of prenatal care. This study presents prospective collected data on MA use and birth outcomes, controlling for most confounders. Materials and Methods This is a retrospective cohort study of women obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
71
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(79 citation statements)
references
References 35 publications
4
71
2
1
Order By: Relevance
“…Unlike studies 48,49 showing that prenatal methamphetamine exposure is associated with lower birth weight and higher incidence of being small for gestational age, we found no group differences in birth weight, which is consistent with a large study 50 of pregnancy outcomes in methamphetamine-using women. These discrepancies may be attributable to differences in racial or ethnic distributions or participant criteria across studies.…”
Section: Discussionsupporting
confidence: 90%
“…Unlike studies 48,49 showing that prenatal methamphetamine exposure is associated with lower birth weight and higher incidence of being small for gestational age, we found no group differences in birth weight, which is consistent with a large study 50 of pregnancy outcomes in methamphetamine-using women. These discrepancies may be attributable to differences in racial or ethnic distributions or participant criteria across studies.…”
Section: Discussionsupporting
confidence: 90%
“…There are limited data on the prevalence of methamphetamine use in pregnancy, with national estimates varying from 0.7% to 5.2% [137]. Recent work shows that methamphetamine use is associated with shorter gestational ages, lower birthweight [139], fetal loss [140], developmental and behavioral deficits [141], gestational hypertension, preeclampsia, and intrauterine fetal death [142]. Fetal outcomes may vary based on exposure timing and duration[139].…”
Section: Stimulantsmentioning
confidence: 99%
“…Recent work shows that methamphetamine use is associated with shorter gestational ages, lower birthweight [139], fetal loss [140], developmental and behavioral deficits [141], gestational hypertension, preeclampsia, and intrauterine fetal death [142]. Fetal outcomes may vary based on exposure timing and duration[139]. Infants with a positive toxicology at delivery were smaller on average compared to infants with methamphetamine exposure during the first trimester only, who were in turn smaller than non-exposed infants [139].…”
Section: Stimulantsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 2016 National Drug Strategy Household Survey found that 1.3 million Australians had used illicit methamphetamine in their lifetime . Obstetric risks associated with methamphetamine use during pregnancy, including placental abruption, hypertension, preterm birth and fetal growth restriction, are becoming increasingly well defined . The effects of methamphetamine on the developing fetus, however, are less well understood.…”
mentioning
confidence: 99%